Elipse™, a Procedureless Gastric Balloon for Weight Loss: a Proof-of-Concept Pilot Study - Machytka, Evzen; Chuttani, Ram; Bojkova, Martina; Kupka, Tomas; Buzga, Marek; Stecco, Kathryn; Levy, Samuel; Gaur, Shantanu (Obesity surgery, 2016)
BACKGROUND: Endoscopic gastric balloons have been used effectively as weight loss devices for decades, but the requirement for endoscopy and sedation poses several limitations. The goal of this pilot study was to evaluate the safety and performance of a prototype version of Elipse™, a procedureless gastric balloon. METHODS: Eight patients (mean BMI = 31.0 kg/m(2)) participated in this study. Each patient swallowed one Elipse™ balloon intended to remain in the stomach for 6 weeks, self-empty, and then pass. Each balloon was filled with 450 mL of filling fluid. Patients returned every 2 weeks for abdominal ultrasound. No specific diet or exercise plan was prescribed. RESULTS: All eight patients successfully swallowed the device. The most common adverse events were nausea and vomiting. There were no serious adverse events, and all balloons were excreted safely. Despite not being prescribed a diet or exercise plan, all eight patients lost weight. In 6/8 patients, the balloon remained full through 6 weeks, self-emptied, and passed. In one patient, the balloon appeared partially collapsed on ultrasound after 11 days and was endoscopically punctured. One asymptomatic patient elected to have the balloon endoscopically punctured after 19 days. Both balloons passed in the stool after 4 days. In both cases, endoscopic examination of the upper GI tract showed no abnormalities. CONCLUSIONS: This pilot study demonstrates the safety and performance of Elipse™, a procedureless gastric balloon for weight loss. Future studies will test a commercial design filled to 550 mL intended to last in the stomach for at least 12 weeks.
Keywords: obezita; hmotnostní úbytek; Humans; lidé středního věku; Overweight; Intragastric balloon; žaludeční balónek; Female; mladý dospělý; dospělí; Nausea; výsledek terapie; lidé; Gastric Balloon; Vomiting; Weight loss; pilotní projekty; Pilot Projects; Adult; ženské pohlaví; Male; Middle Aged; Treatment Outcome; zvracení; Young Adult; Obesity; mužské pohlaví; nauzea; Gastric balloon; Weight Loss